Nitric oxide participates in sucrose–TOR signaling during meristem activation in Arabidopsis thaliana - Lando, Ana Paula; Terrile, María Cecilia; De Marco, María Agustina; Rodriguez, Marianela; Martínez Noël, Giselle María Astrid (Springer, 2025)
Nitric oxide (NO) constitutes a signal molecule that regulates important target proteins related to growth and development and also contributes to metabolic reprogramming that occurs under adverse conditions. Taking into account the important role of NO and its relationship with Target of Rapamycin (TOR) signaling in animals, we wondered about the putative link between both pathways in plants. With this aim, we studied a TOR-dependent process which is the reactivation of the root apical meristem (RAM) in Arabidopsis thaliana. We used pharmacological and genetic tools to evaluate the relationship between NO and TOR on the sugar induction of RAM, using SNP as NO donor, cPTIO as NO scavenger and the nitrate reductase (NR) mutant nia2. The results showed that sucrose (SUC)-mediated TOR activation of the RAM requires NO and that NO, in turn, participates in the regulation of TOR signaling. Interestingly, TOR activation induced by sugar increased the NO levels. We also observed that NO could mediate the repression of SnRK1 activity by SUC. By computational prediction we found putative S-nitrosylation sites in the TOR complex proteins and the catalytic subunit of SnRK1, SnRK1.1. The present work demonstrates for the first time a link between NO and TOR revealing the complex interplay between the two pathways in plants.